Combined Use of Shear Wave Elastography, Microvascular Doppler Ultrasound Technique, and BI-RADS for the Differentiation of Benign and Malignant Breast Masses - Wang, Bin; Chen, Yu-Yuan; Yang, Si; Chen, Zhen-Wen; Luo, Jia; Cui, Xin-Wu; Dietrich, Christoph F.; Yi, Ai-jiao (Frontiers in Oncology, 2022)
Objective：To evaluate the value of the combined use of breast imaging reporting and data system (BI-RADS), the qualitative shear wave elastography (SWE) and AngioPLUS microvascular Doppler ultrasound technique (AP) for distinguishing benign and malignant breast masses. Materials and Methods: A total of 210 pathologically confirmed breast lesions in 210 patients were reviewed using BI-RADS, the qualitative SWE and AP. The sensitivity, specificity, negative predictive value, positive predictive value, accuracy and the area under the receiver operating characteristic curve (AUC) of BI-RADS and the combination of qualitative SWE and/or AP with BI-RADS, were compared, respectively. Results: Compared with using BI-RADS alone, the combination use of qualitative SWE and/or AP with BI-RADS had higher AUC values (P<0.001). Besides, the combination of qualitative SWE and AP with BI-RADS had the best diagnostic performance for differentiating benign and malignant masses. When AP and SWE were combined with BI-RADS, 49/76 benign masses were downgraded from BI-RADS category 4a into BI-RADS category 3, while no benign masses were upgraded BI-RADS category 3 into BI-RADS category 4a. Three sub-centimetre malignant masses were downgraded BI-RADS category 4a into BI-RADS category 3, three malignant masses remain BI-RADS category 3 due to benign manifestation in both AP and qualitative SWE, 5/6 of them were sub-centimetre, 4/6 of them were intraductal carcinoma. The sensitivity, specificity, PPV, NPV, accuracy and AUC were 91.0%, 81.1%, 69.3%, 95.1%, 84.3% and 0.861 (95% confidence interval [CI], 0.806, 0.916) (P<0.001), respectively. Compared with BI-RADS alone, the sensitivity slightly decreased, while the specificity, PPV, NPV and accuracy were significantly improved. Conclusion: Combination of qualitative SWE and AP with BI-RADS improved the diagnostic performance in differentiating benign from malignant breast lesions, which is helpful for avoiding unnecessary biopsies, however, we should be careful about the downgrading of sub-centimetre BI-RADS 4a category lesions.